2010
DOI: 10.1103/physrevb.82.035402
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature ordering of dilute graphene antiferromagnets

Abstract: We employ large-scale quantum Monte Carlo simulations to study the magnetic ordering transition among dilute magnetic moments randomly localized on the graphene honeycomb lattice, induced by long-ranged RKKY interactions at low charge carrier concentration. In this regime the effective exchange interactions are ferromagnetic within each sublattice, and antiferromagnetic between opposite sublattices, with an overall cubic decay of the interaction strength with the separation between the moments. We verify expli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 45 publications
(71 reference statements)
6
18
0
2
Order By: Relevance
“…Let us note that, in general, the integral approximation is valid for low p (see also Refs. [35,36]).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Let us note that, in general, the integral approximation is valid for low p (see also Refs. [35,36]).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Thus, an inhomogeneous but unfrustrated antiferromagnetic ground state can be expected for randomly placed moments. Such order is predicted to persist at finite temperature even in this 2d situation due to the long-range nature of the RKKY interaction [81]. Departing from charge neutrality, a crossover to standard metallic behaviour is expected.…”
Section: Multiple Impurities: Rkky Interaction and Magnetic Ordermentioning
confidence: 99%
“…Theoretical studies suggest that the crucial role in determining the magnetic properties of graphene is played by the the localized electron states. Exchange between them is realized by the longranged Ruderman-Kittel-Kasuya-Yoshida (RKKY) interactions mediated by conducting electrons [2][3][4][5][6]. For the centres localized on the same sublattice, ferromagnetic order is expected, whereas interactions between centres localized on two various sublattices lead to antiferromagnetic ordering analogous to the state of a diluted antiferromagnet [2][3][4].…”
mentioning
confidence: 99%
“…Exchange between them is realized by the longranged Ruderman-Kittel-Kasuya-Yoshida (RKKY) interactions mediated by conducting electrons [2][3][4][5][6]. For the centres localized on the same sublattice, ferromagnetic order is expected, whereas interactions between centres localized on two various sublattices lead to antiferromagnetic ordering analogous to the state of a diluted antiferromagnet [2][3][4]. Several authors have demonstrated the importance of the edge states and single-atom point defects [5][6][7][8].…”
mentioning
confidence: 99%